Improving health in at-risk youth through Photovoice. (December 2017) - Bashore, Lisa; Alexander, Gina K; Jackson, D Lynn; Mauch, Paige
Photovoice is a practical method to allow at-risk youth to express the environmental influences in their lives at school, at home, and in their community. This project emerged from an interprofessional collaboration between social work and nursing that focused on school health. The purpose was to explore the factors influencing the mental and emotional health using photographs by students in a largely Hispanic middle school. Ten students were recruited and consented but only eight completed the project. The SHOWeD method was used to assist the students to formally reflect upon their photographs. Data analysis was conducted using content analysis to identify themes presented the students' reflections. The themes were staying healthy, stress dealing with anger/frustration, maintaining friendships and communication, recognizing bullying, and planning for the future. Reflections aided students to provide rich details about how the school environment influences their mental and emotional health. The use of Photovoice is a reasonable method for at-risk youth to explore and describe their environment. Nurses, social workers, parents, and school leaders can use the new knowledge about how the school environment influences the health of students to develop tools to support a healthy school and community environment.